Development of a Problem-Based Learning Module on Elements, Compounds, and Mixtures to Enhance Eighth-Grade Students’ Critical Thinking Skills - Imam Setiawan; Baskoro Adi Prayitno; Bowo Sugiharto (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop and evaluate a Problem-Based Learning (PBL) science module supplemented with Mind Maps on the topic of elements, compounds, and mixtures to enhance the critical thinking skills of eighth-grade students. The research objectives were to: 1) describe the module's characteristics, 2) examine its feasibility, and 3) test its effectiveness. The development followed the Borg and Gall procedure, comprising ten systematic steps. The module's feasibility was assessed using the Aiken’s V validity test, while its impact on critical thinking skills was analyzed using ANCOVA. The results demonstrated that: 1) The developed module possesses distinctive characteristics, integrating PBL with Mind Maps, which promotes active student engagement and provides direct learning experiences to foster critical thinking. 2) The module is highly feasible for classroom use, supported by a strong Aiken’s V validity value of 0.85. 3) The module is statistically effective in improving students' critical thinking skills. This conclusion is substantiated by the ANCOVA test results, which showed a highly significant value of p <0.001, confirming a notable enhancement in critical thinking abilities after the implementation of the module. The study successfully validates the module as a viable and effective learning tool.